2017
DOI: 10.1002/jbm.a.36290
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and immunogenicity of elastin‐like recombinamer biomaterials in mouse models

Abstract: Novel thermo‐sensitive elastin‐like recombinamers (ELRs) containing bioactive molecules were created for use as a biomimetic biomaterial for tissue regeneration. For effective use for in vivo applications, it is essential to ensure that they do not induce adverse inflammatory, immune, or allergic responses that inhibit tissue repair. Therefore, we sought to establish a pre‐clinical approach to evaluate biocompatibility in experimental mice using ELRs as a prototype biomaterial. First, we measured in vitro prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Elastin-like polypeptides (ELP) are a class of protein biopolymers composed of repeating five-amino acid units (VPGxG, where x is any amino acid except proline) with unique physical properties [1] and many advantages as drug carriers [2]. ELPs are relatively biologically inert, having little to no cytotoxicity [3,4,5] and low immunogenicity [6,7]. Also, being proteins rather than chemically synthesized polymers, they degrade in vivo into non-toxic natural amino acids [8].…”
Section: Introductionmentioning
confidence: 99%
“…Elastin-like polypeptides (ELP) are a class of protein biopolymers composed of repeating five-amino acid units (VPGxG, where x is any amino acid except proline) with unique physical properties [1] and many advantages as drug carriers [2]. ELPs are relatively biologically inert, having little to no cytotoxicity [3,4,5] and low immunogenicity [6,7]. Also, being proteins rather than chemically synthesized polymers, they degrade in vivo into non-toxic natural amino acids [8].…”
Section: Introductionmentioning
confidence: 99%
“…Enormous efforts are still underway for developing novel and effective gene delivery systems based on biocompatible nanomaterials to transfer the target genes to the tumor site [167,191,192]. For example, researchers have developed an elastin-like recombinant (ELR) and specific MUC1 aptamers for intracellular delivery of the MUC1 gene to breast tumors [193].…”
Section: Breast Cancer Therapymentioning
confidence: 99%
“…Gonzalez de Torre et al (2018) described the "clickable" properties of ELRs and used electrospinning to prepare bioactive fibers from clickable ELRs with no crosslinking agent added. In another study, Changi et al (2018) developed thermo-sensitive ELRs which contained bioactive molecules and showed good biocompatibility and limited immunogenicity in BALB/c and C57BL/6 mouse models. Moreover, some functional sequences, such as growth factors, can be attached via chemical reactions to ELRs molecule or can be directly inserted into main sequences of ELRs through recombinant techniques (Flora et al, 2019).…”
Section: Elrs-based Dermal Matrixesmentioning
confidence: 99%